Determination of DynamicElastic Properties of Anah Formation, Near Rawa city / Western Iraq Using Ultrasonic Technique - Khorshid, Salman Z.; Al-Awsi, Munther D.; Kadhim, Emad H. (Iraqi Journal of Science, 2020)
The aim of the current study is to determine the elastic properties of carbonate rocks using ultrasonic method. Forty rock samples of Anah formation were collected at different depths from four wells drilled at the study area . The relationship between wave velocities and elastic properties of rocks was defined. Regression analyses to define these relations were applied. The results indicate that the elastic properties of the rocks show a linear relationship with both P- and S-wave velocities. The best relationship was obtained between both Young’s modulus and Shear modulus with Vs in the determination of the coefficient ( R2 ), with values of 0.91 and 0.94, respectively. Bulk modulus and Lameâ€™s constant were better correlated with Vp than with Vs in the determination of R2,with values of 0.92 and 0.83, respectively. Poissonâ€™s ratio showed a good correlation using the ratio of Vp/Vs in the determination of R2, with a value of 0.81. The main output of this study shows that the ultrasonic method is a useful tool for the prediction of the elastic dynamic properties of sample rocks and that it can be used as an economical , simple and non- destructive method, especially for engineering purposes.